Infections in gynecology and obstetrics. Puerperal infections. - Trelles, Juan (2015)
Puerperal infection is a serious problem for any hospital department of Obstetrics, because it's very important cause of maternal morbidity and mortality, it prolongs hospital stay, increasing the use of expensive drugs and requires care specialists. Women with postpartum fever in need of intensive and systematic assessment, trying to make an early diagnosis to quickly administer treatment.